2020
DOI: 10.2217/fon-2020-0120
|View full text |Cite
|
Sign up to set email alerts
|

Deviations from a clinical pathway post pancreatoduodenectomy predict 90-day unplanned re-admission

Abstract: Aim: To determine the frequency and relevance of deviations from a post pancreatoduodenectomy (PD) clinical care pathway. Materials & methods: A retrospective analysis using a prospectively maintained database of a post-PD clinical care pathway was carried out between May 2016 and March 2018. Patients were divided based on the number of factors deviating from the clinical care pathway (Group I: no deviation; Group II: deviation in 1–4 factors; Group III: deviation in 5–8 factors). The analysis included pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In clinical practice, the patient is the center, and the work of multiple departments, including professional departments and administrative departments, is integrated; it emphasizes horizontal contact and communication between departments. The clinical pathway is not a standard of behavior, but a kind of guidance or advice, and does not deprive the doctor of autonomy [ 25 ]. It proposes the best diagnosis and treatment plan discussed and approved by experts, which reduces the difference in treatment effects due to different levels of doctors and protects the interests of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the patient is the center, and the work of multiple departments, including professional departments and administrative departments, is integrated; it emphasizes horizontal contact and communication between departments. The clinical pathway is not a standard of behavior, but a kind of guidance or advice, and does not deprive the doctor of autonomy [ 25 ]. It proposes the best diagnosis and treatment plan discussed and approved by experts, which reduces the difference in treatment effects due to different levels of doctors and protects the interests of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Braga et al (65) highlighted that patients with early postoperative low compliance to the ERAS® pathway had a higher incidence of complications. Karunakaran et al (100) showed that less than 10% of patients following PD display a 100% compliance and deviation from >50% of clinical pathway components is associated with an increased risk of 90-day (but not 30-day) readmission, which signals the importance of continued close surveillance in these patients (102).…”
Section: Eras® In Pancreatic Surgerymentioning
confidence: 99%
“…Most studies have used length of hospital stay (LoS) to evaluate the performance of their care pathways. Taking a closer look at the relationship between adherence to individual pathway components and LoS, failure to remove the naso-gastric tube (NGT) on POD2 (103), intolerance to liquid diet on post-operative day (POD) 3 ( 103), inability to tolerate solid food by POD 5 (94,100), re-insertion NGT (100), need to continue antibiotics beyond POD 2 (100) and inability to remove drain on the designated day (94) were predictors of longer hospitalization. This leads one to infer that post-operative pancreatic fistula (POPF), delayed gastric emptying (DGE), and infectious complications are major causes of deviations.…”
Section: Eras® In Pancreatic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown an association between low compliance to ERAS protocols and decreased clinical outcomes such as more overall, respiratory, infectious, and major complications (Clavien-Dindo III), longer length of hospital stay and more readmissions following PD. 4,5 Although epidural analgesia is recommended over intravenous morphine in the recent ERAS Society guideline for PD (1), the optimal pain management remains controversial, and the reported use of epidural analgesia varies from 11 to 85%. 6 There are only a few well-conducted randomized controlled pain management trials reporting on patients undergoing PD [7][8][9] and to date the role of transversus abdominis plane blocks has not been assessed for these patients.…”
Section: Introductionmentioning
confidence: 99%